2021
DOI: 10.1002/acr.24194
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intermittent and Constant Knee Pain Patterns With Knee Pain Severity and With Radiographic Knee Osteoarthritis Duration and Severity

Abstract: Objective To examine the relation of knee pain patterns to pain severity and to radiographic osteoarthritis (OA) severity and duration. Methods The Multicenter Osteoarthritis Study is a longitudinal cohort of older adults with or at risk of knee OA. Participants’ Intermittent and Constant Osteoarthritis Pain (ICOAP) scores were characterized as 1) no intermittent or constant pain, 2) intermittent pain only, 3) constant pain only, and 4) a combination of constant and intermittent pain. Knee pain severity was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Using the Intermittent and Constant Osteoarthritis Pain scale (ICOAP), developed in response to the aforementioned qualitative work, we have recently shown that the patterns of intermittent, constant, and constant AE intermittent pain are associated with the duration of disease, worsening pain severity, and radiographic OA, thus supporting the qualitative work on which the scale is based (5). In light of this evidence and our increasing understanding of altered pain signal processing, different pain mechanisms may underlie these qualitative pain patterns and the transitions from one to another.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Using the Intermittent and Constant Osteoarthritis Pain scale (ICOAP), developed in response to the aforementioned qualitative work, we have recently shown that the patterns of intermittent, constant, and constant AE intermittent pain are associated with the duration of disease, worsening pain severity, and radiographic OA, thus supporting the qualitative work on which the scale is based (5). In light of this evidence and our increasing understanding of altered pain signal processing, different pain mechanisms may underlie these qualitative pain patterns and the transitions from one to another.…”
Section: Introductionmentioning
confidence: 88%
“…Initial psychometric testing of the scale demonstrated good validity and reliability (10). The ICOAP was obtained in a knee-specific manner, inquiring about symptom type and severity over the prior 7 days, following a previously validated method (5,11). ICOAP pain patterns were defined as follows: 1) no intermittent or constant pain, 2) intermittent pain only (of at least mild severity and with a frequency of at least sometimes), 3) constant pain only (of at least mild severity), and 4) a combination of constant and intermittent pain.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…This was done separately for both the lunchtime and early evening pain; as the patterns of pain were similar, we decided to present only the lunchtime pain scores. In line with previous literature by Carlesso et al who have written extensively about the idea of OA causing two types of pain: intermittent (variable) and constant (stable), 20 we also explored a two-class model (based on variance only), which included constant (stable) pain and intermittent (variable) pain.…”
Section: Questionnaire Datamentioning
confidence: 99%
“…An important aspect to consider when choosing a potential outcome of symptomatic OA is the fact that in early stage OA, pain can be absent for prolonged periods of time, with short and very sudden short flare-ups. 55,56 For patients with early-stage OA, it is this intermittent pain that is extremely burdensome. 57 When pain is highly fluctuating, one can question the clinical relevance of a single measure in time of something like "pain during walking" or the PASS.…”
Section: Measuring the Incidence Of Osteoarthritis Illnessmentioning
confidence: 99%